2007
DOI: 10.1371/journal.pone.0000748
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication Stress Is a Determinant of Chronological Lifespan in Budding Yeast

Abstract: The chronological lifespan of eukaryotic organisms is extended by the mutational inactivation of conserved growth-signaling pathways that regulate progression into and through the cell cycle. Here we show that in the budding yeast S. cerevisiae, these and other lifespan-extending conditions, including caloric restriction and osmotic stress, increase the efficiency with which nutrient-depleted cells establish or maintain a cell cycle arrest in G1. Proteins required for efficient G1 arrest and longevity when nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 88 publications
12
115
1
Order By: Relevance
“…The overall leftward shift in fluorescence intensity in starving planktonic populations (e.g., Fig. 2A, 17-d) may be evidence of DNA degradation (24); indeed, it has been argued that such cells become apoptotic (25). By contrast, flow cytometry confirmed that immobilized yeast fed ad libitum ceased replicating by day 5, was in G1-like arrest, and was not apoptotic (Fig.…”
Section: Nondividing Well-fed Yeast Shows No Loss In Viability Duringmentioning
confidence: 84%
See 1 more Smart Citation
“…The overall leftward shift in fluorescence intensity in starving planktonic populations (e.g., Fig. 2A, 17-d) may be evidence of DNA degradation (24); indeed, it has been argued that such cells become apoptotic (25). By contrast, flow cytometry confirmed that immobilized yeast fed ad libitum ceased replicating by day 5, was in G1-like arrest, and was not apoptotic (Fig.…”
Section: Nondividing Well-fed Yeast Shows No Loss In Viability Duringmentioning
confidence: 84%
“…In fact, survivorship of encapsulated rim15Δ mutants is comparable to that of starved planktonic rim15Δ mutants in extended batch culture (20%) (77). Reduced viability of the deletion strain may be attributed to its inability to completely arrest, which leads to replicative stress (24,78), and/or to diminished stress resistance, which is essential for stationary-phase survival. Given that RIM15 is highly expressed in encapsulated but not in planktonic yeast, and given that encapsulated wild-type but not rim15Δ cells cease to reproduce and show extended CLS, we conclude that differential expression of RIM15 facilitates cell cycle arrest and increases stress resistance in immobilized yeast.…”
Section: Growth Arrest and Longevity In Immobilized Yeast May Be Relamentioning
confidence: 97%
“…In SP cultures, auxotrophs have been shown to be genetically unstable and rely on the DNA damage checkpoint to retain viability (Weinberger et al, 2007). One potential solution to this problem is to add fourfold more of the required compounds than are typically added (Powers et al, 2006;Wei et al, 2008).…”
Section: Ylr108c Ylr338w(opi9) Ymr169c(ald3) Ymr170c(ald2) Ymr2mentioning
confidence: 99%
“…Lifespan data did not support this hypothesis, but surprisingly, we found that strains with high Ty1 copy number had extended lifespan when cells were grown either in synthetic medium or in rich medium in the presence of a low dose of the ribonucleotide reductase inhibitor hydroxyurea (HU). Hydroxyurea can stimulate Ty1 mobility and causes DNA replication stress, and replication stress has been correlated with reduced yeast chronological lifespan Weinberger et al 2007Weinberger et al , 2013. However, lifespan extension in high Ty1 copy-number strains did not appear to be due to high retrotransposition levels or substantial differences in DNA replication stress.…”
mentioning
confidence: 97%